Características del palmito fresco y procesado al horno de la palma de pejibaye (Bactris gasipaes) - Ortiz, A.J; Calderón, S; Arguello, O (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Some physical characteristics and chemical composition of the raw and oven baked heart (palmito) of pejibaye palm {Bactris gasipaes H B. K.) are reported. The weight yield per unit of length (ke/m) was found to be closely related to the diameter of the stem (r=00319) by an exponential type equation Y= 0.069 exp (0.54X) The heart represent about twenty per cent weight of the stem for the same unit of length. The effect of number of layers on the acceptability and weight loss during the oven process was studied for different conditions of temperature and processing time. The best results were obtained by oven at 250 and 300 C during 25 minutes. Both oven conditions showed similar results with two layers, however general acceptance increased with the oven at 300 C/2S min with three layers. Preliminary tests have shown the product is highly perishable, it was found to be contaminated during the cooling state prior to packaging This situation could be overcome by appropriate design of cooling chamber for this purpose.